Cash for Work in Sierra Leone : A Case Study on the Design and Implementation of a Safety Net in Response to a Crisis - Andrews, Colin; Ovadiya, Mirey; Ribes Ros, Christophe; Wodon, Quentin (World Bank, Washington, DC, 2013)
This paper presents an assessment of the first phase (2008?2009) of Sierra Leone's cash for work program based on a qualitative and quantitative analysis examining program design features, main processes and impact. The assessment highlights that while cash for work was an appropriate crisis response, the challenge of achieving good targeting should not be underestimated. Findings from the assessment point to high inclusion errors of non?poor population quintiles, despite the program apparently many rules of best practice in program design. The assessment points to a series of factors to explain targeting performance, and future strategies consider mixed methods with a greater emphasis on the role of communities in affecting overall outcomes. The assessment notes areas of success during implementation, including the impact of the program in promoting cohesion amongst youth groups, as well as women. In this sense the assessment points to future strategies and options for moving cash for work forward under its expanded incarnation of the Youth Employment Support Project. Through the use of light qualitative and quantitative methods, the paper also advocates for similar assessments where monitoring and evaluation capacity are weak and time constraints tight.